Raising entrepreneurial capital - Vinturella, John B., 1942-; Erickson, Suzanne M. (Oxford : Academic, 2003)
This book focuses on capital raising for the entrepreneural venture----it covers the debt vs. equity decision, the options available to new and smaller businesses, and the ramifications of rapid growth and financing.
Includes bibliographical references and index.
aug 06/06/13
Loans
Keywords: Venture capital; Small business -- Finance; Entrepreneurship